From the point of view of a gastroenterologist: Is the ulcer malign, or benign? (Annals of Medical Research, 2021)
Aim: To evaluate the opinion of the physician and the necessity of repeat endoscopy to be performed in the prediction of malignancy in patients with endoscopic detection of gastric ulcer.Materials and Methods: Patients who underwent endoscopy for any reason between 01.01.2019-01.10.2019 and who had gastric ulcer were included in the study. The physician who performed the endoscopy was asked to report their opinion about the ulcer endoscopically. By comparing the biopsy results taken from the ulcer and the opinion of the physician who performed the endoscopy, the accuracy of the doctor's prediction about the ulcer was evaluated.Results: A total of 411 patients, 186 women (45.3%), 225 men (54.7%), were included in the study. In 126 (30.7%) of the 411 patients who participated in the study, ulcers were malignant. 106 (84.1%) of these patients were also considered to have definitive malignancy by the physician as a result of endoscopy. physician opinion was suspicious in 17 (13.5%) of them. Although only 3 (2.4%) patients were considered to have benign ulcers, the pathology result was malignant ulcer. Considering all patients, sensitivity was calculated as 84.1%; specificity 98.5%; positive predictive value 96.3%; negative predictive value 93.3%; AUC 0.914; and p 0.05 for the prediction of the physician.Conclusion: The prediction of the physician performing the endoscopy in the gastric ulcer followed with endoscopy is very valuable. In the end, we think that the control endoscopy should be individualized.
Keywords: Endoscopy; gastric cancer; gastric ulcer